2013
DOI: 10.4049/jimmunol.1301300
|View full text |Cite
|
Sign up to set email alerts
|

Alternative End-Joining and Classical Nonhomologous End-Joining Pathways Repair Different Types of Double-Strand Breaks during Class-Switch Recombination

Abstract: Classical nonhomologous end-joining (C-NHEJ) and alternative end-joining (A-EJ) are the main DNA double-strand break (DSB) repair pathways when a sister chromatid is not available. However, it is not clear how one pathway is chosen over the other to process a given DSB. To address this question, we studied in mouse splenic B cells and CH12F3 cells how C-NHEJ and A-EJ repair DSBs initiated by the activation-induced deaminase during IgH (Igh) class-switch recombination (CSR). We show in this study that lowering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 70 publications
2
54
0
Order By: Relevance
“…In the absence of some c-NHEJ factor, CSR is still able to occur, although with reduced efficiency and with increased microhomology in the S-S junctions, a process called alternative end joining. Furthermore, Cortizas et al (21) recently showed that factors of the C-NHEJ and A-EJ have the same kinetics of recruitment to the S regions. Therefore, CSR may occur at the G 1 /S border possibly because this is the only time that factors involved in NHEJ, A-EJ, and HR pathways can simultaneously participate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of some c-NHEJ factor, CSR is still able to occur, although with reduced efficiency and with increased microhomology in the S-S junctions, a process called alternative end joining. Furthermore, Cortizas et al (21) recently showed that factors of the C-NHEJ and A-EJ have the same kinetics of recruitment to the S regions. Therefore, CSR may occur at the G 1 /S border possibly because this is the only time that factors involved in NHEJ, A-EJ, and HR pathways can simultaneously participate.…”
Section: Discussionmentioning
confidence: 99%
“…3D and Ref. 21). LMB treatment alone caused a strong increase of nuclear AID accumulation, in agreement with a previous report (24) (Fig.…”
Section: Cdks Regulate the Level Of Nuclear Aidmentioning
confidence: 90%
See 1 more Smart Citation
“…Chromatin immunoprecipitation was performed as previously described (11). In short, activated or nonactivated B cells were cross-linked with 1% formaldehyde for 20 min at room temperature, and the reaction was stopped by addition of glycine to 125 mM final concentration.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%
“…2D), we were interested in how the mutation influenced nuclear translocation and chromatin association. To address this, we performed chromatin immunoprecipitation in combination with real-time PCR using primers specific for the AID binding site in the Ig Sm locus (11). DNA was isolated from wild-type and AID R112H B cells at 0 or 48 h When assessing peripheral B cell development and function, before and after immunization with TNP-SRBCs, AID R112H mice had an increased number of total B cells in the spleen compared with wild-type littermate mice (Fig.…”
Section: Identification Of the R112h Mutation In Aicdamentioning
confidence: 99%